Determinação do coeficiente e expoente de escoamento em esquadrias nacionais, para análise de infiltração de ar em edificações - Santos, Henrique Zenker dos (Universidade do Vale do Rio dos Sinos, 2016)
Developed countries have continued growth in global energy consumption rates. One of the most important factors is related to the use of air conditioners to the comfort conditions inside buildings’ maintenance, which such a part already reaches consumption values higher than the industry and transportation sectors. It is known that consumption due to air conditioning directly affects the energy and environmental performance of a building and therefore the house’s quality and the people’s life. In Brazil, this process leads to a big increase in public spending, with many consequences of economic and social order. Information from the Ministry of Mines and Energy indicate that 20% of the energy consumed in the country is used for supplying homes. This scenario tends to evolve due to the constant housing market releases, derived from housing plans stimulated by the federal government (such as “Minha Casa Minha vida”), in consequence of the housing deficit registered in the country. Related to this, it is observed the low construction standards of buildings and the use of materials and frames of low quality that lead to thermal load inefficiencies. Engineers and architects spend a part of their activities in creating scenarios for evaluating the thermal load calculation and vulnerability due to the influence caused by air infiltration into the environment. The infiltration rate of a building is managed by the established relationship by a power law equation, which is characterized by a flow coefficient "C" and a flow exponent "n" (usually on the value of 0.667 [-]). This work shows for an aluminum window, sliding template, the flow coefficient C = 0.028 [dm³/s.m.Pan] and the flow exponent "n" 0.552 [-]. For PVC window, integrated model, the flow coefficient C = 0.022 [dm³/s.m.Pan] and the exponent flow "n" 0.605 [-].
Keywords: Condicionadores de ar; Edificações; Infiltração; Vazamento; Coeficiente de escoamento; Expoente de escoamento; Equação da lei da potência; Eficiência energética; Air conditioners; Buildings; Infiltration; Air leakage; Flow coefficient; Flow exponent; Power law equation; Energy efficiency; ACCNPQ::Engenharias::Engenharia Mecânica